Representação social da ortotanásia: significados atribuídos por enfermeiros e médicos na unidade de terapia intensiva - Bisogno, Silvana Bastos Cogo (2008)
In this research, it proposes an approximation of the meaning given by nurses and doctors in relation to the practice of orthothanasia. Thus, tracing out the purpose of analyzing the social representations of nurses and doctors, working in the Intensive Care Unit (ICU), in the practice of orthothanasia and how these representations influence the professional activities. This is an exploratory type of search based on a qualitative approach, which adopts as the theoretical framework of social representations Moscovici. Was developed in the adult ICU of a public hospital located in the geographic center of Rio Grande do Sul (RS) and the population were five nurses and five physicians. It was decided to semi-directed. The period of data collection occurred from January to March of 2008. Ethical issues were considered in the research as required by Resolution 196/96 of the National Health Council, for the conduct of research with human beings. After analyzing the content of Bardin, it was possible to identify some distancing and approximations of the representations. The proliferation vocabulary designating orthothanasia is pervaded by doubt and lack of concept and its applicability, and this action can easily be distorted or confused with euthanasia. The orthothanasia appears so latent in speeches, and professionals do not refer directly to your action. The term is related to the possibility of death occurs at the right time without unnecessary pain and suffering. Refer know exactly what the practice is illegal in the orthothanasia hospital. The representations of nurses in orthothanasia are directed to the alleviation of suffering, and its operation confirmed by the methods of non cardiorespiratória resuscitation (CPR) in patients deemed not investível. The representations about orthothanasia the physicians are built on the same perspective, as opposed to suffering from the patient and not the result leads RCR, however direct his attention to the fear and anguish that this decision creates the risk of legal punishment. Discuss the matter of the practice of orthothanasia was not simply consider it as something mechanical, but its performance against the context of a dynamic routine that tries to mask it, simply because there is no amparos in different areas, whether in medicine the jurisdiction. In fact, the orthothanasia, which is installed in the hospital, was perceived by practitioners as the viable option to treat the death as an inevitable and constant in order to counter any prolongation of human suffering. Thus, it is necessary to consider the context of the patient die in dignity, from the actions that aim to understand it as deadly.